Prediction of Nonunion in the Diaphyseal Segment of Long Bones in Adults Using the RUST Score and Modified RUST Score - Anupam Gupta; C Prasanna; BK DinakarRai (Journal of Orthopedics and Joint Surgery)
Background: The study analyzed the radiographic union score for tibia (RUST) and modified radiographic union score for tibia (mRUST), a time-based scoring system for categorizing delayed union and nonunion, to assess 3-month fracture healing in the diaphyseal segment of long bones. Delayed union patients were treated with bone marrow or platelet-rich plasma injections and dynamization to reduce the rate of nonunion. Materials and methods: In this study, randomized patients were prospectively analyzed by RUST and modified RUST scores after internal fixation of tibial, humeral, and femoral fractures (AO/OTA tibia 42A, femur 32A, and humerus 12A). The aim was to define delayed union or nonunion based on the scoring system and time factor. The delayed union patients were offered simple secondary interventions. Patients at risk of nonunion were identified. Results: Out of 64 patients, only 48 patients completed regular follow-ups. The rate of nonunion was 6.25. The mean score of 5.33–5.67 at 3 months was consistent with those in previously published works on the tibia and femur. The 3-month mRUST score for humeral fractures had no predictive value. Conclusion: Lower 3-month RUST scores for tibial and femoral fractures are strongly associated with nonunion, and there is a need for secondary intervention. However, lower modified RUST scores for humeral fractures at 3 months had no prognostic value for detecting nonunion.